Reflexiones sobre la historia del Perú fuera del Perú - Rosas Moscoso, Fernado (2020)
ResumenEn el contexto del Bicentenario de la Independencia del Perú, en este artículo ofrecemos un enfoque de la historia patria casi totalmente dejado de lado; el investigar y difundir la historia de territorios que en épocas pretéritas pertenecieron a nuestro país y que actualmente no forman parte de su espacio. Palabras clave: historia del Perú, Bicentenario, Independencia.  AbstractThe territorial extension of a singular state or a politic organization changes throughout time and the current reality determines the limits of the historical process and makes us lose on sight the different dimensions that hold the course of time. It involves pondering about the importance of these variabilities and the role of the political construction from that time. The vision of Peru, concerning the territories that in our current time do not belong to our country, and the reappraisal of the forgotten and delayed phases. The case of Peru is unique due to the existence of three phases: Prehispanic phase, Hispanic domination phase and Republican phase.Keywords: State, territorial evolution, History of Peru, Peruvian history outside present Peru